PERBANDINGAN HASIL BELAJAR IPS TERPADU SISWA MELALUI MODEL DL DAN PjBL - Dita Widiastuti; Pujiati Pujiati; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
This research aims to know the difference of students learning results in IPS Terpadu subject and the effectiveness of DL and PjBL in IPS Terpadu subject at the seventh grade students of SMP Negeri 1 Pagelaran. This research used experimental method method with a comparative approach. The population were 319 students and the sample was two classes which divided into 31 students of experiment class and 32 students of control class. The sample was taken by using cluster sampling. The data were collected by using interview, observation, documentation and test. The data were analyzed by using T-test Two Sample Independent and Formula of N-Gain. The result of this research showed that: (1) There is a difference of average of students learning results in IPS Terpadu subject who taught by using DL and students who taught by using PjBL, (2) There is a difference of effectiveness between the use of DL and PjBL.Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar IPS Terpadu siswa dan efektivitas model pembelajaran DL dan PjBL pada mata pelajaran IPS Terpadu siswa kelas VII di SMP Negeri 1 Pagelaran. Penelitian menggunakan metode eksperimen dengan pendekatan komparatif. Populasi berjumlah 319 siswa dan sampel sebanyak dua kelas yang terdiri dari 31 siswa kelas eksperimen dan 32 siswa kelas kontrol. Sampel ditentukan melalui teknik cluster sampling. Pengumpulan data melalui wawancara, observasi, dokumentasi, dan tes. Analisis data menggunakan T-test Dua Sampel Independen dan rumus N-Gain. Hasil penelitian ini menunjukkan bahwa: (1) Ada perbedaan rata-rata hasil belajar IPS Terpadu siswa yang diajar menggunakan model DL dengan siswa yang diajar menggunakan PjBL, (2) Ada perbedaan efektifitas antara model DL dan model PjBL.Kata kunci: DL, hasil belajar, PjBL